The mediating effect of organizational justice : moderating roles of sende of coherence and job complexity on the relationship between servant leadership and work engagement - Öner, Zeynep Hale (My University, 2008)
Bu araştırmanın ana hedefi, hizmetkar yöneticilik özellikleri gösteren yöneticilerin, örgütsel adalet algısına yaptığı etki üzerinden çalışanların işe kapılmaları (work engagement) üzerine olan etkisini incelemektir. Bu çalışmada, adaletin üç boyutu: paylaşım, işlemsel ve etkileşim örgütsel adalet algısı olarak incelenmiştir. Ayrıca, çalışanların tutarlılık anlayışı (sense of coherence), ve yapılan işin karmaşıklık düzeyi algıları da modelde şartlı değişken olarak test edilmiştir. Ayrıca paternalistik yöneticilik özellikleri ile hizmetkar yöneticilik özellikleri arasındaki korelasyon da incelenmiştir. 305 beyaz yaka çalışan ile yapılan araştırmada, çalışmanın amacına uygun olarak paternalistik yöneticilik, hizmetkar yöneticilik, örgütsel adalet, işe kapılma, tutarlılık anlayışı ve işin karmaşıklığı ölçekleri kullanılmıştır. Hizmetkar yöneticilik ölçeğinin Türkiye’ye adaptasyonu yapılmıştır. Tutarlılık anlayışı ölçeğinin bilgimiz dahilindeki ilk türkçeleştirme çalışma ve uygulaması yapılmıştır. Ayrıca işin karmaşıklığı ölçeğine ek olarak bir ölçek geliştirilmiştir. Araştırma analizleri sonucu, çalışanlar hizmetkar liderlik özelliklerine sahip yöneticileri ilişkisel, diğergamlık, katılımcı ve güçlendirici özellikleri ile algılamışlardır. Paternalistik yöneticilik özellikleri ile hizmetkar yöneticilik özellikleri arasında yüksek korelasyon ortaya çıkmıştır. Algılanan örgütsel adalet algısı ve işe kapılma arasında anlamlı pozitif doğrusal ilişki bulunmuştur. Algılanan örgütsel adalet, hizmetkar yöneticilik ve işe kapılma değişkenleri arasında tam ara değişken olarak ortaya çıkmıştır. Tutarlılık anlayışı hizmetkar yöneticilik ile örgütsel adalet algısı arasındaki ilişkide, ve işin karmaşıklık düzeyi de örgütsel adalet algı ve işe kapılma ilişkisi üzerinde hipotez edildiği gibi şartlı değişken olarak rolleri kanıtlanamamıştır. Hizmetkar yöneticilik özelliklerinin örgütsel adalet algısı üzerine olan manidar etkisinde çalışan bireyin tutarlılık anlayışının ilişkiyi etkileyecek düzeyde bir etkisi saptanamamıştır. Çalışan bireyin yaptığı işin karmaşıklık düzeyi de çalışanın örgütsel adalet algısı ile işe kapılma arasındaki ilişkiyi etkileyecek düzeyde bir etki yapmadığı saptanmıştır.

The main purpose of this study is to analyze the effect of perceived servant leadership characteristics of managers on the perceived organizational justice and work engagement of the employees. Within this framework, the moderating effect of the employees’ sense of coherence and the nature of job i.e. the job complexity on the relationship between the relevant variables is also investigated. A sample of 305 employees from low and middle management is utilized. For the purpose of the study; paternalistic leadership,servant leadership, organizational justice, sense of coherence, job complexity and work engagement questionnaires are used. The servant leadership questionnaire is adapted to the Turkish setting and job complexity questionnaire is supplemented with an additional measure developed by the researcher. To prove the correlation between the paternalistic leadership characteristics with the servant leadership characteristics of the managers, the research question ‘ is there a correlation between servant leadership and paternalistic leadership ?’ was also analyzed. The servant leadership proved to be conceptualized with relational, altruistic, participative and empowering dimensions. The perceived procedural and distributive justice were significantly positively related to ‘vigor and dedication’, ‘work absorption’ factors of work engagement. It is worth noticing that the perceived procedural justice had more effect on work engagement, especially on the vigor and dedication dimensions than the distributive justice perception.Analysis indicated that perceived paternalistic characteristics of managers highly, positively correlated with the perceived servant leadership qualities of managers. There was a positive relationship between perceived organizational justice and worker engagement. The perceived organizational justice totally mediated the relationship between servant leadership and work engagement. As to the moderating effects of sense of coherence and job’s complexity nature , there was no supporting evidence of moderation of any of the two variables in the model. Thus the sense of coherence did not moderate the relationship between the perceived servant leadership and organizational justice variables, and the job’s complexity level did not prove to moderate the hypothesized relationship between organizational justice and work engagement.
Keywords: İş Tatmini; Örgütsel Davranış; Yönetici-Çalışan İlişkisi